(untitled) (Nepal Agriculture Research Journal, 2009)
An experiment was conducted at agronomy farm of Agriculture research Station, Tarahara, Nepal for three consecutive years viz 2000/2001,2001/2002, and 2002/2003 to evaluate the effects of different cultural practices on leaf blight diseases of wheat caused by Bipolaris sorokiniana under terai conditions. The experiment was conducted in factorial Randomized Complete Block Design with four replications. Four factors, two wheat verities RR-21 and Nepal 297,two number of irrigations (two and three irrigations), two doses of Nitrogen fertilizer viz. 60kg N/ha and 120 kg N/ha and two dates of sowing of wheat were examined. Different yield components, grain yield (kg/plot) and disease severity were recorded to judge the effects of these factors on severity of leaf blight of wheat. Nepal Line 297 had significantly less AUDPC based on flag leaf infection and whole plan as compared to RR-21. Number of irrigations had no significant effect on AUDPC, as there was frequent rain during experimental period. Doses of Nitrogen fertilizer had significant effect on AUDPC based on flag leaf infection. It was higher in case of 60 kg N/ha. The third week of November sowing of wheat had lower value of AUDPC as compared to December sowing. Plant height, panicle lengths were highly significantly higher in case of RR-21 as compared to Nepal-297. Thousand kernel weight, and grain yield kg/ha were significantly higher in Nepal-297. All agronomic parameters except thousand kernel weight and number of tillers/plan were significantly higher in 120kg N/ha. The third week of November sowing of wheat had less plant height and panicle length, higher thousand kernel weight and more grain yield. Leaf blight severity was highly significantly less in case of Nepal-297. Doses of Nitrogen fertilizer had significant effect on plant height, panicle length, thousand kernel weight, percentage flag leaf infection and AUDPC based on flag leaf infection. Based on the results of three years of experimentations, it can be concluded that Nepal-297 had less disease, number of irrigations had no effect on disease severity, higher doses of nitrogen fertilizer had less flag infection and late sowing of wheat also had less disease. Numbers of irrigation’s effects were inconclusive as there were frequent rains during experimentation period. Based on above conclusion, it is recommended that growing wheat verity like Nepal-297, use of higher doses of nitrogen fertilizer and sowing of wheat / first week of Dec help in minimizing the severity of leaf blight. However late sowing had lowered grain yield. Key words: AUDPC; culture practices; disease management; leaf blight DOI: 10.3126/narj.v7i0.1870 Nepal Agriculture Research Journal Vol.7 2006 pp.63-69